Unveiling The Nexus: Exploring the Impact of Behavioral Finance on Green Finance Initiatives - Chuahan, Rahul; Chavda, Kishan (Indonesian Journal Publisher, 2024)
This research paper delves into the dynamic landscape of global climate finance during the fiscal years of 2021/2022, examining the collaborative efforts of public and private actors in addressing the multifaceted challenges posed by climate change. The equitable distribution of financial resources reflects a shared commitment to transformative action, with a focus on critical sectors such as energy, transport, and buildings and infrastructure. Both sectors emphasize the transition to renewable energy, sustainable transportation, and climate-resilient urban development. Public finance plays a pivotal role by directing support to relatively underserved sectors, including Agriculture, Forestry, and Other Land Use (AFOLU), water and wastewater management, and industry. This targeted intervention ensures inclusivity in climate action and contributes to broader sustainable development goals. The financial commitments not only reduce carbon footprints but also foster innovation, job creation, and economic resilience. The collaborative model of climate finance observed during this period sets a precedent for future endeavors, emphasizing a holistic and inclusive approach. The research suggests potential avenues for future studies, such as assessing the long-term impact of climate finance, evaluating evolving patterns in public-private collaboration, and exploring the integration of climate finance within global policy frameworks. Ultimately, this research contributes to the ongoing discourse on climate resilience, offering insights into the interconnectedness of financial commitments, sustainable development, and the global fight against climate change.